Written production in Portuguese as a Foreign Language/Second Language classroom: when and how to intervene - Cruz, Sara Oliveira da (Universidade Estadual Paulista, 2021)
One of the recurring concerns of Portuguese as Foreign Language/Second Language (PFL/PSL) teachers, especially in the early stages of their teacher training, encompasses the correction of written production. The objective of this work is to present aspects that involve the "correction" of textual productions of PFL/PSL students and discuss when and how to intervene in these productions, based on data presented in Cruz (2019), which were generated from the observations of classes and interviews carried out with all participants; the implementation of a set of activities and also the internship reports of the trainee teachers. Initially, this article presents the concepts of language, teaching, and learning that led and lead the researcher's actions outside and inside the classroom; then, it discusses aspects that may involve the “correction” of the aforementioned text productions and, finally, the work presents some proposals for the intervention of the teacher in the written productions.